2016
DOI: 10.3233/wor-162398
|View full text |Cite
|
Sign up to set email alerts
|

Burden of lupus on work: Issues in the employment of individuals with lupus

Abstract: The paper presents innovative strategies that include early interventions and how employers andco-workers can provide helpful support that includes job accommodations to individuals with lupus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
0
11
1
Order By: Relevance
“…Performance in these executive function domains is necessary for work productivity, particularly for jobs with a high cognitive requirement (38). This potential evidence of impairment may partially explain the substantial employment issues faced by SLE patients (3941), although we did not detect any differences in cognitive performance by employment in this study. We found that, as expected, scores were not associated with age, sex, and race, given that the scores were adjusted for these characteristics.…”
Section: Discussioncontrasting
confidence: 61%
“…Performance in these executive function domains is necessary for work productivity, particularly for jobs with a high cognitive requirement (38). This potential evidence of impairment may partially explain the substantial employment issues faced by SLE patients (3941), although we did not detect any differences in cognitive performance by employment in this study. We found that, as expected, scores were not associated with age, sex, and race, given that the scores were adjusted for these characteristics.…”
Section: Discussioncontrasting
confidence: 61%
“…This disease has significant adverse effects on many areas in life. The employment rate in patients with SLE is often affected by their disability and frequent sick leaves [11]. Authors Ekblom-Kullberg S. et al [12] also confirmed that sick leave and absence in work are two or three times more frequent in patients with SLE than in the healthy population.…”
Section: Discussionmentioning
confidence: 91%
“…Fatigue can cause dramatic impairments in mood (14), diminish social aspects of life (15), lead to an inability to perform routine daily activities (16), and limit physical activity and work (17). Consequently, fatigue can severely affect well-being and has a financial burden on the individual, family, and society (1821).…”
Section: Introductionmentioning
confidence: 99%